Lipid nanoparticles biocompatibility and cellular uptake in a 3D human lung model - Marina Barroso Pereira Pinheiro (2020)
Aim: Design nanostructured lipid carriers (NLC) to facilitate drug delivery to tuberculosis-infected areas, exploiting macrophage mannose receptors and assess their uptake in a 3D human lung model. Materials & methods: NLCs and mannosylated-NLCs were synthetized and characterized. Their uptake and biocompatibility were tested in a 3D human lung model. Results: The formulations have appropriate size (170-202 nm) and morphology for lung deposition. Cell membrane integrity was maintained and no significant pro-inflammatory cytokine (IL-1β, IL-8 and TNF-α) secretion or morphological changes were observed 24 h post nanoparticles exposure. NLCs and mannosylated NLCs were distributed in the apical side of the lung tissue, both in macrophages and in epithelial cells. Conclusion: NLCs are biocompatible carriers and can be used for pulmonary drug delivery.